Decentralized feedback stabilization of multiple nonholonomic agents - Dimarogonas, Dimos V.; Kyriakopoulos, Kostas J.; Loizou, Savvas (My University, 2004)
This paper represents an extension of our previous work, on multiagent navigation to the case of decentralized control of multiple nonholonomic vehicles. Our main motivation comes from the field of air traffic management systems and from the field of micro robotic multiagent systems. A discontinuous feedback control scheme, based on dipolar navigation fields, is implemented and integrator backstepping is applied to suppress chattering behavior. The methodology has guaranteed global convergence and collision avoidance properties, which are verified by nontrivial computer simulations.
Keywords: Computer simulation; Feedback control systems; Lyapunov functions; Algorithms